2014
DOI: 10.1099/mic.0.075762-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IncI1-Iγ and IncFIA-FIB type plasmids in extended-spectrum β-lactamase-producing Klebsiella pneumoniae strains isolated from the NICU of a North Indian hospital

Abstract: We studied the molecular mechanism of resistance in extended-spectrum b-lactamase (ESBL)-producing Klebsiella pneumoniae isolated from a neonatal intensive care unit (NICU) of one of the hospitals in North India. A total of 3000 clinical samples were collected from a NICU (January 2009 to February 2011), of which 523 strains were K. pneumoniae positive and 262 of them were ESBL-producing K. pneumoniae strains. All of the ESBL-producing clinical isolates were susceptible to carbapenems. However, the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…Previous studies have shown that the prevalence rate of ESBL-and carbapenemase-producing K.pneumoniae isolates can be varied from 19% to 60% in different countries [22][23][24][25]. To support this result, in our study, 51% of collected isolates were ESBLproducers while 49% of them were carbapenemaseproducers.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that the prevalence rate of ESBL-and carbapenemase-producing K.pneumoniae isolates can be varied from 19% to 60% in different countries [22][23][24][25]. To support this result, in our study, 51% of collected isolates were ESBLproducers while 49% of them were carbapenemaseproducers.…”
Section: Discussionsupporting
confidence: 78%
“…Bonnin et al 10 , speculated that IncFII, plasmid replicons endemic to Indian subcontinent, might play a major role in the dissemination of bla NDM gene. This narrow host range, multireplicon plasmid, was also reported to be a frequent carrier of ESBLs, especially bla CTX-M 14 16 23 31 . Interestingly, the prevalent plasmid in bla NDM-1 -producing isolates in this region was also found to be a variant of IncFII, IncFII K .…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of ESBL and MBL producers observed in this study and the observation of co-production of these two enzymes by two isolates was in agreement with the findings of the above-mentioned studies. ESBL producers are reported to be often resistant to multiple antibiotics 16 24 . In our study also 60 per cent of the isolates were found to be resistant to all of the antibiotics tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta-lacatmases are enzymes coded by specific gene and produced in bacteria to hydrolyze antibiotics and hence cause drug resistance against antibiotics a major health problem. A total of about hundreds of variants of each groups of beta-lactamases have been identified and documented in form of manuscripts and databases in the public domain [3][4][5]. The structural and function diversity of these enzymes are remarkable as evident from the fact that a single mutation may changed its activity towards antibiotic hydrolysis.…”
mentioning
confidence: 99%